Enantioselective Bioaccumulation and Dissipation of Soil‐Associated Metalaxyl Enantiomers in Tubifex. Issue 1 (31st October 2013) - Di, Shanshan; Liu, Tiantian; Lu, Yuele; Zhou, Zhiqiang; Diao, Jinling
ABSTRACT Many pesticides are chiral compounds and stereochemistry is an important factor for any reaction of chiral structures in biological systems. In this study, experiment about bioaccumulation of the two metalaxyl enantiomers in Tubifex (Oligochaeta, Tubificida) was conducted in laboratory aquatic ecosystems. Terrestrial soil spiked with two dose levels of metalaxyl was employed as the artificial bottom substrate. A method of determination of metalaxyl enantiomers in tubifex tissue, soil and overlying water were developed by HPLC. During a 14‐day exposure, concentrations of metalaxyl in tubifex increased with the of soil concentration, however, the enantioselective bioaccumulation was only detected at high‐dose exposure group, with the preferential accumulation of (‐)‐(R)‐metalaxyl. The bioturbation activity of tubifex decreased water clarity and released soil‐associated metalaxyl to overlying water. In those experiments where tubifex was exposed to metalaxyl from soil, pore water and overlying water, each route contributed to the total body burden, and our results indicated the pore water and soil are the primary exposure routes for high‐dose exposure concentration treatment. Chirality 26:33–38, 2013. © 2013 Wiley Periodicals, Inc.